Preparation and Management of In-service Inspection Schedule Program in Nuclear Power Plants. (June 2020) - Li, Tian; Xue, Donglin; Yan, Hai; Yin, Qin
Abstract: In-service Inspection (ISI) schedule program for nuclear island equipment was of the important part of ISI program file system in nuclear power plants (NPPs), which acted as a connecting link. Based on ISI rules for the mechanical components of PWR nuclear islands (RSE-M) and the plant ISI general program, the preparation method for schedule program of CPR1000 units were presented. It focused on the analysis and discussion of the existing problems during the preparation, upgrade and management process and some targeted suggestions were put forward. It may lay a foundation for a further optimization of the ISI program file system and the smooth implementation of the ISI activities.